Sei sulla pagina 1di 269

∇ · E

× E +

1

B

c

∂t

∇ · B

× B 1

c

E

∂t

=

=

=

=

4πρ

0

0

4π

c

J,

· ( × ) = ( × ) · = · ( × ) = ( × ) · = · ( × )

( × ) · ( × ) = ( · )( · ) ( · )( · )

( · ) ( · )

× ( × ) =

( · ) =

× (∇ × ) + × (∇ × ) + ( · ∇) + ( · ∇)

∇ × ( × ) = (∇ · ) (∇ · ) + ( · ∇) ( · ∇)

∇ · ( × ) = · (∇ × ) · (∇ × )

∇ × (φ ) = φ(∇ × ) × (φ)

∇ · (φ ) = φ(∇ · ) + · ∇φ

(φψ) = φψ + ψφ

∇ × (∇ × ) = (∇ · ) − ∇ 2

∇ · (∇ × ) = 0

∇ × (φ) = 0

∇ × f (r)] = 0

∇ × = 0

∇ · = 3

V θ2 ψ + ψ · ∇θ d 3 r = S θ ψ · da

ˆ

V (φ2 ψ ψ2 φ) d 3 r = S (φψ ψφ) · da

ˆ

V (∇ · ) d 3 r = S · da

ˆ

S (∇ × ) · da = C · d

ˆ

V ∇ × d 3 r = S ˆ

× da

S

ˆ

× (ψ) da = C ψ d

V ψ d 3 r = S ψ da

ˆ

 

 

 

∇ · E B

c ∂t

∇ · B

E

∇ × B 1

× E + 1

c ∂t

=

4πρ

=

0

=

0

=

4π

J.

c

E

:

,

B

:

,

ρ :

3 ,

J :

c :

2 , .

1 =

1 3 × 10 9 .

3 × 10 9 .

=

1 300 1 .

=

E B ρ J E(r, t) B(r, t) ρ(r, t) J(r, t) O r = (x, y, z) = (x 1 , x 2 , x 3 ) r t

E(r, t) = (E x (r, t), E y (r, t), E z (r, t)) ,

1

E

c ∂t

E x (r, t) = E x (x, y, z, t)

i

E i (r, t) = E i (x 1 , x 2 , x 3 , t) i = 1, 2, 3 x i

E ( r , t ) B ( r , t ) ∇ φ (

E(r, t) B(r, t)

φ(x, y, z) = φ ∂x

, ∂φ , ∂φ

∂z

∂y

.

∇ · E = E ∂x x

+ ∂E y ∂y

+ ∂E z ∂z

.

∇ × E =

ˆz

E x E y E z =

∂x

∂y

∂z

∂E y

∂z

E

∂t

=

∂E z ∂y

+ E ∂x z

∂E x , ∂E y

∂t

∂t

, ∂E z ∂t

∂E x ∂z

+ E ∂y x

∂E y ∂x

ˆz.

 

.

t r

t (∇ · E)

=

=

=

∂t ∂E x

   

∂x

+ ∂E y ∂y

+ ∂E z ∂z ∂ 2 E z

2 E x

+

2 E y

+

∂x∂t

∂y∂t

∂z∂t

∇ · E ∂t .

t

· E = 4π ρ .

∂t

∂t

E

∂t

c∇ · (∇ × B) 4π∇ · J = 4π ρ ∂t .

∇ · (∇ × B) = 0

∂ρ

∂t

+ ∇ · J = 0.

< 0

∇· J > 0

ρ

t > 0

∇· J < 0

q e = 1.6 × 10 19

ρ

∂t

ρ J E B q v E B q F = q E + v

ρ J

E B q v E B q

F = q E + v

E B E E B E B E B ρ J

× B .

c

B ∂t = 0

E(r) B(r)

E

∂t

ρ ∂t = 0.

= 0

,

,

∇ · E = 4πρ

∇ × E = 0

+

∇ · B = 0

∇ × B = 4π J.

c

q 1 q 2 r 1 r 2

c      q 1 q 2 r 1 r 2 q 2

q 2 q 1

F q 2

= k

q 1 q 2

r 1 | 3 (r 2 r 1 ) ,

|r 2

k k 1

F q 2 = F q 1 .

E(r) r q r

F(r) = qE(r).

F(r) q E(r)

F ( r ) q E ( r ) E q E ( r ) r

E q

E(r) r q 0

E(r) = lim

q0

F(r)

q

.

r 2 q 1 q 2 0

E(r 2 ) = lim

q 2 0

F q 2

q

2

=

q

1

|r 2 r 1 | 3

(r 2 r 1 ) .

q 1 | r 2 − r 1 | 3 ( r 2 − r 1

E(r) r q r 1

E(r 2 ) q 1 r q r 1

E(r) =

q r 1 | 3 (r r 1 ) . |r

q O r 1 = 0

E(r) = q 3 r = q 2 ˆr ,

r

r

r = |r| E B

E 1 E 2

E 1 + E 2 r

q i r i i = 1, 2,

, N

E(r) =

N

i=1

q

i

(r r i )

|r r i |

3 .

= N i =1 q i ( r − r i ) | r − r

r q i r i

q i 0 N N → ∞ ρ r i r q i dq = ρ(r )d 3 r d 3 r

E(r) = ρ(r )

(r r ) |r r |

3

d 3 r ,

r

:

r

:

r r ∇ · E = 4 πρ S A · nˆ da = V

r r

∇ · E = 4πρ

S A · da = V ∇ · A d 3 r.

A V S V S A S ∇ · E = 4πρ V ρ

V ∇ · E d 3 r = 4π V ρ(r) d 3 r,

S E · da = 4πq ,

q S

S E · nˆ da = 4 πq , q S S E S S S

S E S S S S ∇ × E = 0

C A · dl = S (∇ × A) · da.

A S C

S S ∇ × E = 0 C A · d l = S ( ∇

∇ × E = 0 S C

S (∇ × E) · da = 0

C E · dl = 0.

S

∇ × E ) · nˆ da = 0 ⇒ C E · d l =

r σ(r ) E 1 E 2 r S S σ r S S

1 E 2 r S nˆ S σ r S S

h 0 S

S E · da = 2 E 2 · da + 1 E 1 · () da = 4πq

A (E 2 E 1 ) · da = 4π A σ(r ) da.

A 0 r

E 2 (r ) · E 1 (r ) · = 4πσ(r ).

· nˆ − E 1 ( r ) · nˆ = 4 πσ ( r )

C

E C b l

b 0

b0 c

lim

C E · dl = 0.

E · dl = 2 E 2 · dl + 1 E 1 · dl = 0

ˆ

ˆ

l 0 dl dl t dl → −dl t

2

1

E 2 · ˆ t = E 1 · ˆ t.

lim

l0

ˆ

E 2 · t dl

lim

l0

ˆ

E 1 · t dl = 0

σ

σ E z S S E · nˆ da = 4 πq . S A E

E z S

S E · da = 4πq .

S A

E 3

3 E 3 · 3 = 0

S

E 1 = Eˆz 1 = ˆz

E 2 = Eˆz 2 = ˆz

S

E · da

=

1 E 1 · 1 da + 2 E 2 · 2 da

= 1

= 4πq [ A] = 4